Spring fever: collared lemmings warm up above the snow despite predation risk - Demers, Rachel; Desjardins, Émilie; Fauteux, Dominique; Vézina, François; Tam, Andrew; Berteaux, Dominique (Frontiers in Ecology and Evolution, 2025)
Small mammals inhabiting cold climates face high heat losses and thus, high energy demands for body temperature regulation. However, behavioral adaptations, such as seeking refuge from extreme cold in the subnivean space, can reduce the energetic cost of thermoregulation. Using automated cameras, we monitored collared lemmings (Dicrostonyx groenlandicus) at the northern limit of their range, as they surfaced from their snow burrows in spring, to assess the effect of weather variables on the occurrence of this behavior. We hypothesized that lemmings reduce the energetic cost of thermoregulation when they come to the surface of the snow in spring. As expected, the frequency of surface activity increased with air temperature, but decreased with cloud cover and wind speed. In addition, the operative temperature was higher above the snow than below, while snow profiles showed the absence of liquid water in the snowpack. These findings support that lemming surface activity in spring is a behavioral thermoregulation strategy. However, observations of several predators in the study area, combined with vigilance behavior observed in lemmings at the snow surface, stress the risks associated with such exposure on the snow. We therefore suggest that lemmings may face a trade-off between thermoregulation and predation risk. Given that data on lemming winter ecology are scarce, we also exploited this behavior to gather valuable knowledge on molting phenology and reproduction. Overall, our results provide insight into the complex trade-off between thermoregulation and other needs in small mammals inhabiting cold climates, and highlight some potential implications for arctic ecosystem dynamics based on predator-prey interactions.